A meta-model for formulating digital transformation strategies for SMEs: A knowledge management-based approach - Klein, Vinícius Barreto; Todesco, José Leomar; Sell, Denilson (Seven Editora, 2024)
Digital Transformation (DT) is a new socio-technical paradigm that has been reshaping society. The intensification of the use of the most recent digital technologies has triggered the need for significant changes in organizations (e.g. educational institutions, physical commerce), and in their different organizational elements (e.g. processes, technologies, culture). In this context, the problem of small and medium-sized enterprises (SMEs) stands out. They have great value for social well-being due to their ability to generate work. However, they have a long way to go on the path to digital transformation, compared to large companies. Its specific limitations, such as the scarcity of financial resources and the lack of knowledge to deal with DT, accentuate this difficulty. This implies the need to know how to design a more effective DT strategy or process, which makes better use of its scarce resources and which strategically aligns them with the potential of digital technologies. Therefore, with an approach based on knowledge management and interdisciplinary research, the following research question was investigated: how to support SMEs to face challenges and take advantage of the opportunities brought through digital transformation? Therefore, under a systemic view of TD in organizations, a meta-model was proposed, which focuses on the strategic level and initiates the adaptation of business models, through cycles of adaptation and response to new external demands. As theoretical and basic foundations, the Cesm method, the Canvas Business Model, and the organizational resilience mechanisms were used, linked to the Seci knowledge spiral. As a methodological approach, systematic reviews of scientific articles, case studies and business reports were used, combined with the Design Science Research Process (DSRP). The adopted design involved iterative and collaborative steps of conceptual review and refinement of the constructed meta-model, which was subjected to conceptual review through the submission of articles and the analysis of two domain experts in DT. As a final result, the developed artifact is presented, which structures three phases to guide the TD process, focusing on the strategic level of organizations, also recommending steps and samples of support materials (examples of tools to assist TD). As delimitations, it is highlighted that the meta-model does not address elements inherent to the tactical and operational levels of organizations. As limitations, it is pointed out that larger and more diverse samples can be used in the future. Its practical implications are to guide SMEs, indicating where and how to start DT, using phases and steps to guide this process.. As future work, its instantiation in various sectors and organizations of different sizes is recommended, as well as the use of different tools, and measurement of long-term results. DOI:https://doi.org/10.56238/sevened2024.014-003